Inequalities in coverage of COVID-19 vaccination: A population register based cross-sectional study in Wales, UK. Issue 42 (8th October 2021) - Perry, Malorie; Akbari, Ashley; Cottrell, Simon; Gravenor, Michael B.; Roberts, Richard; Lyons, Ronan A.; Bedston, Stuart; Torabi, Fatemah; Griffiths, Lucy
Highlights: First study to examine equality in coverage of COVID-19 vaccination across Wales. Overall vaccination coverage for COVID-19 vaccination is high. Vaccination coverage is lower in more deprived areas and among ethnic minority groups. First vaccine study to use census linkage providing high data coverage on ethnic group. Closing the vaccination equity gap before further waves of infection should be a priority. Abstract: The COVID-19 pandemic has highlighted existing health inequalities for ethnic minority groups and those living in more socioeconomically deprived areas in the UK. With higher levels of severe outcomes in these groups, equitable vaccination coverage should be prioritised. The aim of this study was to identify inequalities in coverage of COVID-19 vaccination in Wales, UK and to highlight areas which may benefit from routine enhanced surveillance and targeted interventions. Records within the Wales Immunisation System (WIS) population register were linked to the Welsh Demographic Service Dataset (WDSD) and central list of shielding patients, held within the Secure Anonymised Information Linkage (SAIL) Databank. Ethnic group was derived from the 2011 census and over 20 administrative electronic health record (EHR) data sources. Uptake of first dose of any COVID-19 vaccine was analysed over time, with the odds of being vaccinated as at 25th April 2021 by sex, health board of residence, rural/urban classification, deprivation quintile and ethnic group presented. Using logistic regression models, analyses were adjusted for age group, care home resident status, health and social care worker status and shielding status. This study included 1, 256, 412 individuals aged 50 years and over. Vaccine coverage increased steadily from 8th December 2020 until mid-April 2021. Overall uptake of first dose of COVID-19 vaccine in this group was 92.1%. After adjustment the odds of being vaccinated were lower for individuals who were male, resident in the most deprived areas, resident in an urban area and an ethnic group other than White. The largest inequality was seen between ethnic groups, with the odds of being vaccinated 0.22 (95 %CI 0.21–0.24) if in any Black ethnic group compared to any White ethnic group. Ongoing monitoring of inequity in uptake of vaccinations is required, with better targeted interventions and engagement with deprived and ethnic communities to improve vaccination uptake.